Execution of Fiduciary Collateral Based on the Decision of the Constitutional Court Number 18/PUU-XVII/2019 - Sofyan Wimbo Agung Pradnyawan; Siti Syahida Nurani; Arief Budiono; Sasongko Sasongko (Indonesian Journal of Law and Policy Studies, 2020)
The Constitutional Court responded to the existence of a debt collector who had been very unsettling by the Constitutional Court by issuing Decision Number 18/PUU-XVII/2019 dated January 6, 2020. Based on the request for a judicial review of Law 42/1999 submitted by husband and wife Apriliani Dewi and Suri Agung Prabowo . Apriliani is a fiduciary who experiences direct losses as a result of creditors' withdrawal of the object of fiduciary security in the form of a car. Both applicants are declared to have legal standing in submitting a request for a judicial review. The Constitutional Court granted it with Decision Number 18/PUU-XVII/2019. In this decision, the execution mechanism for the fiduciary guarantee object was changed by the Constitutional Court as long as it was not provided voluntarily by the debtor. Previously, the Fiduciary Law allowed creditors to execute the object of fiduciary collateral themselves, but now to carry out the execution, creditors must submit an application to the District Court. However, the implementation of direct execution by the creditor without going through the District Court can be done if the debtor admits that there is a default or default in his agreement with the creditor.